FAKTOR-FAKTOR YANG BERHUBUNGAN DALAM PRAKTEK PEMBERIAN ASI SAMPAI ANAK BERUMUR DUA TAHUN DI UPK PUSKESMAS KAMPUNG DALAM KECAMATAN PONTIANAK TIMUR - Nurmayanti, Mega; Suaebah, Suaebah (Pontianak Nutrition Journal, 2018)
In 2010 Coverage of infants aged 0-6 months received exclusive breastfeeding in West Kalimantan only 11.93% while the target was 65% (DHO Prov. Kalbar, 2011) and in 2010 the coverage exclusive breastfeeding in Pontianak at 22.82 % (health Prov. Kalbar, 2011). Based on traffic data in infants aged 0-6 months at Kampung Dalam subdistrict health center UPK East Pontianak in 2012, of 705 infants aged 0-6 months babies only 207 (29.36%) were breastfed exclusively. From the data above, shows the low level of breastfeeding by the mother to her baby. This is due to many factors related to the practice of breastfeeding to their children. This study aims to determine the factors related to the practice of breastfeeding until the child is two years old at Kampung Dalam subdistrict health center UPK East Pontianak. This type of research is observational method used is survey with cross sectional approach. The number of samples examined 80 samples with research time 4 to 11 July 2013. The primary data obtained directly from the respondent by interview using questionnaires while the secondary data obtained from authorized personnel at Kampung Dalam subdistrict health center UPK East Pontianak. Data analysis was performed through univariate and bivariate analyzes were accompanied by a significance test with a confidence level of 95%. Processing data using a computer program with Chi-Square test. The result showed that there was a significant association between knowledge and practice of breastfeeding until the child is two years old at Kampung Dalam subdistrict health center UPK East Pontianak. There is no significant relationship between maternal employment, previous breastfeeding experience and condition of the breast at Kampung Dalam subdistrict health center UPK East Pontianak. Local health authorities are advised to provide information / education by using media to more effectively about breastfeeding, especially the practice of breastfeeding until the child is two years old.